Active liver X receptor signaling in phagocytes in multiple sclerosis lesions. (March 2018) - Mailleux, Jo; Vanmierlo, Tim; Bogie, Jeroen FJ; Wouters, Elien; Lütjohann, Dieter; Hendriks, Jerome JA; van Horssen, Jack
Objective: We sought to determine the liver X receptor (LXR) ligands present in human macrophages after myelin phagocytosis and whether LXRs are activated in multiple sclerosis (MS) lesions. Methods: We used real-time quantitative polymerase chain reaction (PCR) and immunohistochemistry to determine expression of LXRs and their response genes in human phagocytes after myelin phagocytosis and in active MS lesions. We used gas chromatographic/mass spectrometric analysis to determine LXR-activating oxysterols and cholesterol precursors present and formed in myelin and myelin-incubated cells, respectively. Results: Myelin induced LXR response genes ABCA1 and ABCG1 in human monocyte-derived macrophages. In active MS lesions, we found that both gene expression and protein levels of ABCA1 and apolipoprotein E ( APOE ) are upregulated in foamy phagocytes. Moreover, we found that the LXR ligand 27-hydroxycholesterol (27OHC) is significantly increased in human monocyte-derived macrophages after myelin uptake. Conclusion: LXR response genes are upregulated in phagocytes present in active MS lesions, indicating that LXRs are activated in actively demyelinating phagocytes. In addition, we have shown that myelin contains LXR ligands and that 27OHC is generated in human monocyte-derived macrophages after myelin processing. This suggests that LXRs in phagocytes in active MS lesions are activated at least partially by (oxy)sterols present in myelin and the generation thereof during myelin processing.